การพัฒนาระบบวางแผนความต้องการวัตถุดิบโรงงานผลิต เครื่องนุ่งห่ม - ภิญโญ วงค์ษา (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This research was development of materials requirement planning system for case study apparel factory using WebERP enterprise resource planning system program. An objective was to reduce of operation procedures and operation time for materials requirement planning, materials disbursement and materials stock checking also decrease for the difference of materials inventory between database and store. The first step started from data survey for operation procedures and operation time of above processes also the difference of materials inventory between database and store, then install the WebERP program and operation training for employees by related modules before test to run program for 3 months along with those data collecting also related data in order to compare for the result before and after program running test. From the result of data comparison found that, the operation procedure for materials requirement planning process using WebERP was 47% reduced and 51% reduced for average operation time while, the materials disbursement average time was reduced for 23% with equal procedures. For average operation time of fabrics stock checking between database and store, there was 29% reduced and 31% reduced for accessories, also the difference of materials inventory between database and store was reduced to 1% for both materials.